Strategi Pembelajaran Hybrid Berbasis Learning Engagement Era 4.0 Pada Pembelajaran Biologi di SMA Charis Malang - Susanti, Lidia (Edutechnium Journal of Educational Technology, 2024)
Era 4.0 education is technology-based in the learning process, the use of hybrid learning, allows educators to maximize their presence by using existing technology, both asynchronously and synchronously. The advantage of learning engagement used in learning is to present interaction in learning. This study examines four interactions that exist in learning, namely learner to learner interaction, learner to the instructor interaction, learner to content interaction, learner to self-learner interaction. The four interactions were measured using a questionnaire with a Likert scale, the reliability of the questionnaire results was analyzed with Cronbach's Alpha 0.935 and there was a significant correlation with a sig value of 0.00. The use of learning engagement in hybrid learning will stimulate and involve students in learning so that when there is no educator in front of the students, they continue to learn and do the assigned tasks.